2016
DOI: 10.5665/sleep.6102
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of REM Sleep Behavior Disorder in Early Parkinson Disease

Abstract: RBD increased significantly in PD patients from the de novo state to two-year follow-up. We propose RBE being named "prodromal RBD" as it may follow a continuous evolution in PD possibly similar to the spreading of Lewy bodies in PD patients. RBD itself was shown as a robust and stable marker of early PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 25 publications
5
52
0
Order By: Relevance
“…Subjects with isolated increased EMG activity have been reported to develop clinical RBD at follow‐up . Alternatively, one study found that 7% of healthy controls with RBEs and apparently normal EMG activity developed RBD after 2 years . Similarly, a patient with REM sleep without atonia (RSWA) developed dementia with Lewy bodies 3 years later .…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with isolated increased EMG activity have been reported to develop clinical RBD at follow‐up . Alternatively, one study found that 7% of healthy controls with RBEs and apparently normal EMG activity developed RBD after 2 years . Similarly, a patient with REM sleep without atonia (RSWA) developed dementia with Lewy bodies 3 years later .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, three out of the six patients with ICDs who failed to show RSWA at v-PSG (8% of the total group) reported a typical history of dream-enacting behaviours, with two of them presenting brief REM sleep behavioural events during v-PSG, suggesting a ‘minor’ RBD, which is not uncommon in patients with PD 8. This condition was recently shown to represent a ‘prodromal RBD’ in a cohort of patients with PD prospectively assessed over a 2-year period 24. Thus, when pooling patients with v-PSG-confirmed RBD (n=34) and those with ‘minor’ RBD, the cumulative frequency of RBD in patients with ICDs rose to 93%.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects underwent a cardiorespiratory video‐supported PSG (Xltec: Excel Tech Ltd) according to American Academy of Sleep Medicine (AASM) criteria on two consecutive nights; RBD was diagnosed according to criteria established by Schenck et al and the International Classification of Sleep Disorders, 2nd edition (ICSD 2) . For details, see Sixel‐Doring et al…”
Section: Methodsmentioning
confidence: 99%
“…All subjects underwent a cardiorespiratory video-supported PSG (Xltec: Excel Tech Ltd) according to American Academy of Sleep Medicine (AASM) criteria on two consecutive nights; RBD was diagnosed according to criteria established by Schenck et al 10 and the International Classification of Sleep Disorders, 2nd edition (ICSD 2). 11 For details, see Sixel-Doring et al 2,12 REM without atonia was quantified by surface EMG activity of the mentalis muscle during REM sleep according to the method published by the SINBAR group and the cut-off value for 100% specificity was set at a mentalis EMG activity rate of 18.2%. 23 For diagnosis of RBD, study subjects needed to show REM associated motor behavior and/or vocalizations plus an EMG activity rate above the specific cut-off.…”
Section: Polysomnographymentioning
confidence: 99%